PENGARUH BIAYA PRODUKSI DAN HARGA JUAL JAGUNG TERHADAP TINGKAT PENDAPATAN PENJUALAN JAGUNG DI DESA TRI RAHAYU - handoko, handoko; Vonny Tiara Narundana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This research examines the impact of selling prices and production costs on the income of corn farmers in Tri Rahayu village. Primary data for research is information that has been collected both from other people and individuals, such as the results of surveys and observations. Purposive sampling is a sampling method used to collect a sample of 628 respondents; but when the Slovin formula was applied, the results of the sampling methodology yielded only 86 respondents. Multiple linear regression analysis is a method of data analysis performed through SPSS (Statistical Package For Social Science) software. Based on research findings, production costs have a negative impact on the income of corn farmers in Tri Rahayu Village who sell their crops.